2022
DOI: 10.1111/bjd.20958
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of epidermolysis bullosa in England and Wales: data from the national epidermolysis bullosa database*

Abstract: Summary Background The National Health Service (NHS) epidermolysis bullosa (EB) service, established in 2002, offers comprehensive, free care to all patients in England and Wales. Objectives To quantify prevalence, incidence and mortality of EB in England and Wales. Methods Demographic data for patients in England and Wales were collected on a secure electronic database, prospectively from January 2002 to April 2021 and retrospectively for cases prior to 2002. Vital status was verified using central NHS data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Even though a degree of uncertainty in incidence numbers remains, we are confident that our data are reliable, as they are derived from the main EB diagnostic laboratories. Calculations of point prevalence and mortality for EB and its subtypes are subject to more uncertainty, as Germany lacks a national health register that provides such data in other countries, such as Denmark 27 or the UK 10 . To compensate for this limitation, the capture–recapture model in combination with log‐linear models and correction with random effects represents a solid epidemiologic model and was also applied in rare disease epidemiology studies in other countries 22,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though a degree of uncertainty in incidence numbers remains, we are confident that our data are reliable, as they are derived from the main EB diagnostic laboratories. Calculations of point prevalence and mortality for EB and its subtypes are subject to more uncertainty, as Germany lacks a national health register that provides such data in other countries, such as Denmark 27 or the UK 10 . To compensate for this limitation, the capture–recapture model in combination with log‐linear models and correction with random effects represents a solid epidemiologic model and was also applied in rare disease epidemiology studies in other countries 22,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study included 19 EBS patients (24.7%), six JEB patients (7.8%), and 52 DEB patients (67.5%). In contrast, most studies on the prevalence of EB using national EB registries showed EBS to be the most common subtype, accounting for over or close to 50% of all EB cases [ 19 21 ]. Published studies also revealed that EBS as a share of EB is highest in Northern Ireland (88%), followed by Scotland (58%), Australia (56%), the United States (54%), Japan (51%), and Norway (43%), with the lowest occurring in Croatia (16%) [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petrof et al . also provide longitudinal data and show a reduction of birth incidence over the 19‐year period for all types of EB, even when corrected for changes in total population and the number of live births over the period 3 . This shows the ability of robust epidemiological data from a cohort with high case ascertainment to be able to identify important trends.…”
mentioning
confidence: 84%
“…In this issue of the BJD , Petrof et al . describe the EB population of England and Wales and provide epidemiological data from one of the largest EB cohorts reported until now, with over 2500 patients with EB 3 . They report a prevalence of 34·8 and an incidence of 67·8 per million.…”
mentioning
confidence: 99%